Integrating Broussonetia papyrifera and Two Bacillus Species to Repair Soil Antimony Pollutions - Huang, Huimin; Fan, Li; Zhao, Yunlin; Jin, Qi; Yang, Guiyan; Zhao, Di; Xu, Zhenggang (Frontiers in Microbiology, 2022)
Heavy metal resistant bacteria play an important role in the metal biogeochemical cycle in soil, but the benefits of microbial oxidation for plants and soil have not been well-documented. The purpose of this study was to explore the contribution of two Bacillus spp. to alleviate the antimony (Sb) toxicity in plants, and, then, to propose a bioremediation method for Sb contaminated soil, which is characterized by environmental protection, high efficiency, and low cost. This study explored the effects of Bacillus cereus HM5 and Bacillus thuringiensis HM7 inoculation on Broussonetia papyrifera and soil were evaluated under controlled Sb stressed conditions (0 and 100 mmol/L, antimony slag) through a pot experiment. The results show that the total root length, root volume, tips, forks, crossings, and root activities of B. papyrifera with inoculation are higher than those of the control group, and the strains promote the plant absorption of Sb from the soil environment. Especially in the antimony slag treatment group, B. cereus HM5 had the most significant effect on root promotion and promoting the absorption of Sb by B. papyrifera. Compared with the control group, the total root length, root volume, tips, forks, crossings, and root activities increased by 64.54, 70.06, 70.04, 78.15, 97.73, and 12.95%, respectively. The absorption of Sb by root, stem, and leaf increased by 265.12, 250.00, and 211.54%, compared with the control group, respectively. Besides, both B. cereus HM5 and B. thuringiensis HM7 reduce the content of malondialdehyde, proline, and soluble sugars in plant leaves, keeping the antioxidant enzyme activity of B. papyrifera at a low level, and alleviating lipid peroxidation. Principal component analysis (PCA) shows that both B. cereus HM5 and B. thuringiensis HM7 are beneficial to the maintenance of plant root functions and the improvement of the soil environment, thereby alleviating the toxicity of Sb. Therefore, B. cereus HM5 and B. thuringiensis HM7 in phytoremediation with B. papyrifera is a promising inoculant used for bacteria-assisted phytoremediation on Sb contaminated sites.